Oral microbiome dysbiosis may be associated with intra cranial aneurysms - Jing Ma; Fangyu Wang; Yang Zhu; Yu Tian; Chengzhong Du; Lingjun Yan; Chenyu Ding; Dengliang Wang (BMC, 2024)
Abstract Background Although the etiology of aneurysms remains elusive, recent advances in high-throughput sequencing technology and ongoing human microbiome investigations suggest a potential link between microbiome composition and the onset of various human diseases. Objective This study aimed to utilize high-throughput 16 S rRNA gene sequencing to analyze the oral flora bacterial profiles of individuals, comparing patients with intracranial aneurysms to a healthy control group. Importantly, we sought to identify differences in the oral microbiota and offer novel insights and methods for early diagnosis and identification of intracranial aneurysms. Method Saliva samples were collected from 60 patients with cerebral aneurysms (case group) and 130 healthy individuals (control group). The V3-V4 region of the bacterial 16 S rRNA gene was amplified and sequenced using the HiSeq high-throughput sequencing platform to establish the bacterial profile. Sequencing data were analyzed using QIIME2 and Metastats software to compare composition differences and relative abundance at the phylum and genus levels in the oral microbiota of the two groups. Results Significant differences in oral microbiota composition were observed between patients in the case and control groups (P < 0.05). Genus-level identification highlighted key positions occupied by Eubacterium, Saccharimonadaceae, Rothia, Gemella, Streptococcus, Lactobacillales, Phocaeicola, Bacteroides, Saccharimonadales, and Abiotrophia. Conclusion This study revealed noteworthy distinctions in the composition, abundance, and diversity of oral microbiota between intracranial aneurysm patients and healthy controls. These disparities suggest a potential correlation between oral microbiota and the development of intracranial aneurysms, offering new avenues for early diagnosis and intervention. However, limitations such as a small sample size, lack of prospective design, and absence of causal inference warrant further validation and exploration.